Statistical analysis of random telegraph noise in HfO2-based RRAM devices in LRS. (November 2015) - Puglisi, Francesco Maria; Pavan, Paolo; Larcher, Luca; Padovani, Andrea
Abstract: In this work, we present a thorough statistical characterization of Random Telegraph Noise (RTN) in HfO2 -based Resistive Random Access Memory (RRAM) cells in Low Resistive State (LRS). Devices are tested under a variety of operational conditions. A Factorial Hidden Markov Model (FHMM) analysis is exploited to extrapolate the properties of the traps causing multi-level RTN in LRS. The trapping and de-trapping of charge carriers into/out of defects located in the proximity of the conductive filament results in a shielding effect on a portion of the conductive filament, leading to the observed RTN current fluctuations. It is found that both oxygen vacancies and oxygen ions defects may be responsible for the observed RTN. The variations of the current observed at subsequent set/reset cycles are instead attributed to the stochastic variations in the filament due to oxidation/reduction processes during reset and set operations, respectively.